2017
DOI: 10.1039/c6nj03050e
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative method for analysis of mixtures of homologues and stereoisomers of hemicucurbiturils that allows us to follow their formation and stability

Abstract: Cyclic and linear oligomers of hemicucurbiturils have large difference in UV absorbance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Aav and co-workers very recently published a HPLC-UV procedure to quantitatively assess the distribution of products in the reaction mixture of (R,S)-and (all-R)-cychmCB[n]s. [32] In contrast to biotinuril results from Pittelkow, [5] they found that the value of the molar extinction coefficient of the absorption at 210 nm showed no trends with respect to amount of monomeric units in macrocycles or oligomers. In fact, macrocyclic species seemed to possess absorptivities an order of magnitude higher than the oligomers, which was attributed to fewer degrees of freedom in the macrocycles.…”
Section: Cyclohexylhemicucurbit[n]urilmentioning
confidence: 81%
“…Aav and co-workers very recently published a HPLC-UV procedure to quantitatively assess the distribution of products in the reaction mixture of (R,S)-and (all-R)-cychmCB[n]s. [32] In contrast to biotinuril results from Pittelkow, [5] they found that the value of the molar extinction coefficient of the absorption at 210 nm showed no trends with respect to amount of monomeric units in macrocycles or oligomers. In fact, macrocyclic species seemed to possess absorptivities an order of magnitude higher than the oligomers, which was attributed to fewer degrees of freedom in the macrocycles.…”
Section: Cyclohexylhemicucurbit[n]urilmentioning
confidence: 81%
“…General scheme of dynamic formation of CB macrocycles. [50] We speculate that it is due to higher conformational flexibility of these compounds compared to their cyclic analogues. A) Crystal structure of C-shaped 6-membered glycoluril oligomer [40] (CCDC 701740); B) C-shaped dimer of glycoluril with aromatic terminal groups; S-shaped dimer of glycoluril with aromatic terminal groups.…”
Section: Chain Growth Equilibriummentioning
confidence: 93%
“…Though, Scheme 4. [15,50] Also, surprisingly, a very large discrepancy in the UV absorbance between linear and macrocyclic congeners of cycHCs was observed (Table 1). Figure 2.…”
Section: Chain Growth Equilibriummentioning
confidence: 96%
See 1 more Smart Citation
“…Due to the different elution conditions between the HPLC and HPLC-MS systems, the compound retention times on the obtained HPLC chromatograms were not equal, which is why we refrained from assigning MS data to specific peaks on the shown HPLC chromatograms, except for the previously identified cycHC[6] and cycHC [8] (ref [5]). Figure S31.…”
Section: Hplc Chromatograms and Hplc-ms Datamentioning
confidence: 99%